2007
DOI: 10.3892/ijo.31.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferation of human prostate cancer cells by ethanolic extracts of Brazilian propolis and its botanical origin

Abstract: Abstract. Propolis is a resinous substance collected by bees (Apis mellifera) from various tree buds which they then use to coat hive parts and to seal cracks and crevices in the hive. Propolis, a known ancient folk medicine, has been extensively used in diet to improve health and to prevent disease. In the present study, we have evaluated the effects of ethanolic extracts of Brazilian propolis group l2 and bud resins of botanical origin (B. dracunculifolia), and propolis group 3 on proliferation of metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 18 publications
4
53
0
Order By: Relevance
“…The results obtained are in agreement with the results of propolis collected from China [21] . Ethanolic extract of Brazilian propolis showed potent cytotoxicity and apoptosis inducing ability against prostate cancer cell lines also supported our results [22] .…”
Section: Discussionsupporting
confidence: 79%
“…The results obtained are in agreement with the results of propolis collected from China [21] . Ethanolic extract of Brazilian propolis showed potent cytotoxicity and apoptosis inducing ability against prostate cancer cell lines also supported our results [22] .…”
Section: Discussionsupporting
confidence: 79%
“…When the cells were growing in the serum free medium (KGM), propolis groups 12 and 13 showed similar inhibition against the growth of RC-58T/h/SA#4 (LI et al, 2007) and PrEC cells, but group 13 demonstrated higher growth inhibition than group 12, as shown in Figure 3, and two propolis samples showed higher inhibitory efficiency in malignant cells (RC-58T/h/SA#4) than normal prostate epithelial (PrEC). The 50% growth inhibition (GI50) of propolis was 5 μg.mL -1 for propolis group 12 and 2.75 μg.mL -1 for group 13 in RC-58T/h/SA#4 cell, but 8.75 and 3.25 μg.mL -1 in PrEC cell, as shown in Table 2.…”
Section: Inhibition Of Cell Growth By Two Propolis Samplesmentioning
confidence: 93%
“…After treatment for 48 hours, detection reagents (MTS) were added, and cells were incubated for 1 hour. The absorbance was measured at 492 nm in 96-well plate reader (LI et al, 2007). …”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These include flavonoids, polyphenols, phenolic aldehydes, terpenoids, coumarines, amino acids, steroids and inorganic compounds (2). Propolis products originating from Europe and China contain many types of flavonoids and phenolic acid esters (21), whereas propolis of Brazilian origin is composed mainly of artepillin C, terpenoids and prenylated derivatives of p-coumaric acid (22,23). Benzyl caffeate and phenethyl caffeate isolated from the methanol extract of Chinese propolis do exert antiproliferative activity in murine colon carcinoma cells (21).…”
Section: Discussionmentioning
confidence: 99%